Toxoplasma gondii and Neospora caninum infections in sheep and goats in Switzerland: Seroprevalence and occurrence in aborted fetuses - Basso, Walter (2022)
Toxoplasma gondii and Neospora caninum infections are important causes of abortion in ruminants. Besides, meat from T. gondii infected animals represent a major infection source for humans. The occurrence of these protozoan parasites in Switzerland was investigated both, in a nationwide cross-sectional serological survey, and by molecular methods in aborted sheep and goat foetuses. A total of 653 sheep from 143 farms and 748 goats from 164 farms were tested by commercial ELISAs and inconclusive results were defined by immunoblot. Besides, a risk factor analysis for seropositivity was performed. The observed seroprevalences for T. gondii in sheep and goats were 66.3% and 50.5% at the animal level, and 90.9% and 81.1% at the farm level, respectively. For N. caninum, the detected seroprevalences in sheep and goats were 0.8% and 0.9% at the animal level, and 2.8% and 1.8% at the farm level, respectively. Older small ruminants, and sheep (vs. goats) had a higher risk of being seropositive to T. gondii. Alpine grazing in summer was identified as a protective factor for seropositivity to T. gondii in both animal species. Toxoplasma gondii and N. caninum DNA were detected in 6.1% and 2.4% (n = 82), and in 6.8% and 1.4% (n = 73) of the tested ovine and caprine foetuses, respectively. These results suggest the involvement of these parasites in abortions and reveal a high prevalence of T. gondii and lower prevalence of N. caninum infections in small ruminants in Switzerland. They also suggest that consumption of undercooked meat from T. gondii infected sheep and goats may represent a risk for public health.